Economic dispatch considering of electric vehicle in power system network / Yap Jiazhen - Yap, Jiazhen (2017)
The rapid growth of electric vehicle (EV) offers the future transportation industry with high potential solution on environmental concerns. However, this also brings new challenges to the economic and reliability of power network. With the arrival of large-scale electric vehicles, the operation of the system becomes manageably arduous due to the uncontrolled charging nature of electric vehicles. This research will implement hourly economic dispatch (ED) solution considering the arrival of electric vehicles as an additional load to the system. Using recorded hourly load demand data for different weather conditions obtained from the Malaysia Energy Commission, the simulation data is able to emulate the practically of a real power system network. The hourly probability of EV connected to the network and a vehicle remains idle are used to estimate the percentage increased in load when electric vehicles are connected to the network in charging mode. The consolidated load forecasting analysis was assimilated into standard IEEE test case to solve the hourly economic dispatch problem. Different case studies were carried out to understand the effect of electric vehicles when they are connected to the network in charging mode. From the developed ED solution, it is understood that electric vehicles have a valley filling effect during non-peak hours and higher peak load during peak hours. As a measure to moderate the uncontrolled charging of EV, a control charging scheme is proposed. With this scheme, it could be observed that the total operating cost and generated power is reduced as compared to uncontrolled charging.